Anemia incidence and nutritional status in children with uncorrected congenital heart disease at a teaching hospital in a developing country - Amelia, Putri; Lubis, Nydia Akrami; Efendy, Elmeida; Amelia, Rina; Kannady, Johnson (Heart Science Journal, 2026)
Background: Congenital heart disease (CHD) remains a major contributor to pediatric morbidity and mortality, accounting for an estimated 251,247 infant deaths globally in 2017. In Indonesia, the incidence is approximately 8 per 1,000 live births. Both cyanotic and acyanotic CHD can impair nutritional status, while malnutrition may predispose to anemia and worsen clinical outcomes. Objective: To compare anemia prevalence and nutritional status between children with cyanotic and acyanotic CHD and to identify factors associated with anemia. Methods: This retrospective study analyzed medical records of pediatric CHD patients at Adam Malik Hospital, Medan, Indonesia, from 2023 to 2024. Nutritional status was assessed using standard anthropometric indices. Group comparisons were performed using the Mann–Whitney U and chi-square tests. Multivariable logistic regression was used to identify independent predictors of anemia. Result: A total of 170 patients were included, equally distributed between cyanotic and acyanotic CHD. Tetralogy of Fallot (35.9%) was the most common diagnosis. Severe underweight was observed in 38.8% of patients, while most had normal height-for-age, weight-for-height, and BMI-for-age. Anemia was significantly less frequent in cyanotic than acyanotic CHD (22.4% vs 63.5%, p < 0.001). No significant differences in overall nutritional status were found between groups. However, weight-for-height was independently associated with anemia, indicating the role of acute malnutrition. Conclusion: Anemia differs between cyanotic and acyanotic CHD despite similar nutritional status. Acute malnutrition appears to be a key determinant, highlighting the importance of early nutritional assessment.